A new species of Poliaspoides MacGillivray (Hemiptera, Diaspididae) on Bambusa siamensis (Poaceae) imported into Turkey - Ulgenturk, Selma; Pellizzari, Giuseppina (Zootaxa, 2013)
The adult female and first-instar nymph of a new species of armoured scale insect, Poliaspoides bambusae sp.n. (Diaspididae), is described and illustrated. The new species was collected in Turkey on imported ornamental Bambusa siamensis (Poaceae) from an unknown source.